Intrinsically disordered region of talin’s FERM domain functions as an initial PIP2 recognition site [research data] - Buhr, Jannik; Franz, Florian; Gräter, Frauke (Universität, 2023)
Focal adhesions (FAs) mediate the interaction of the cytoskeleton with the extracellular matrix (ECM) in a highly dynamic fashion. talin is a centr...
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 15.02.2023
Keywords: Forschungsdaten; Datenbank